Identifikasi Knowledge Transfer Menggunakan Pendekatan Siemens Maturity Level - Widiatuti, Mariska Aprisciliana; Pertiwi, Asri (Sekolah Tinggi Ilmu Manajemen dan Ilmu Komputer ESQ (STIMIK ESQ), 2017)
This study aims to understand and identify the process of new knowledge creation in Information Systems Program at STIMIK ESQ. Identification is conducted by approach of Siemens Maturity Level through observation and interview to 21 informants at STIMIK ESQ. The result of this research is the model of new knowledge creation at program study of Information Systems which is explained in Siemens Maturity Level at repeated level. Although creation of new knowledge is inhibited, but there is knowledge creation in the subject of technopreneurship, which is occurred through experience learning and exploring.